Organizational behavior - Robbins, Stephen P. 1943-; Judge, Tim (Pearson Education, 2024)
For undergraduate and graduate courses in organizational behavior. The world's most successful organizational behavior text Organizational Behavior provides the information you want, in the language your students understand. Reflecting the most recent research and events within the field of OB, the 19th Edition continues its hallmark focus on clear writing, cutting-edge content, and intuitive pedagogy. There's a reason why Robbins and Judge's OB textbooks have educated millions of students and have been translated into 20 languages: because of a commitment to provide engaging, cutting-edge material that helps students understand and connect with this important field of study.